Human Mesenchymal Stromal Cells Attenuate Graft-Versus-Host Disease and Maintain Graft-Versus-Leukemia Activity Following Experimental Allogeneic Bone Marrow Transplantation. (22nd January 2015) - Auletta, Jeffery J.; Eid, Saada K.; Wuttisarnwattana, Patiwet; Silva, Ines; Metheny, Leland; Keller, Matthew D.; Guardia-Wolff, Rocio; Liu, Chen; Wang, Fangjing; Bowen, Theodore; Lee, Zhenghong; Solchaga, Luis A.; et al.
Abstract: We sought to define the effects and underlying mechanisms of human, marrow-derived mesenchymal stromal cells (hMSCs) on graft-versus-host disease (GvHD) and graft-versus-leukemia (GvL) activity. Irradiated B6D2F1 mice given C57BL/6 BM and splenic T cells and treated with hMSCs had reduced systemic GvHD, donor T-cell expansion, and serum TNFα and IFNγ levels. Bioluminescence imaging demonstrated that hMSCs redistributed from lungs to abdominal organs within 72 hours, and target tissues harvested from hMSC-treated allogeneic BMT (alloBMT) mice had less GvHD than untreated controls. Cryoimaging more precisely revealed that hMSCs preferentially distributed to splenic marginal zones and regulated T-cell expansion in the white pulp. Importantly, hMSCs had no effect on in vitro cytotoxic T-cell activity and preserved potent GvL effects in vivo. Mixed leukocyte cultures containing hMSCs exhibited decreased T-cell proliferation, reduced TNFα, IFNγ, and IL-10 but increased PGE2 levels. Indomethacin and E-prostanoid 2 (EP2) receptor antagonisms both reversed while EP2 agonism restored hMSC-mediated in vitro T-cell suppression, confirming the role for PGE2 . Furthermore, cyclo-oxygenase inhibition following alloBMT abrogated the protective effects of hMSCs. Together, our data show that hMSCs preserve GvL activity and attenuate GvHD and reveal that hMSC biodistribute to secondary lymphoid organs wherein they attenuate alloreactive T-cell proliferation likely through PGE2 induction. Stem Cells   2015;33:601–614